Cutaneous Metastatic Undifferentiated Carcinoma to the Mandibular Gingiva: A Rare Case Report - Atarbashi Moghadam, Dr.Saede; Lotfi, Ali; Atarbashi-Moghadam, Fazele (Journal of Dental School, 2023)
Objectives Metastasis to the oral cavity is a rare phenomenon. Basal cell carcinoma (BCC) is the most common skin malignancy, followed by squamous cell carcinoma (SCC) and melanoma. Nevertheless, BCC rarely metastasizes, and most cases of cutaneous metastasis to the oral cavity include melanoma and SCC. Oral metastatic lesions are not typical differential diagnoses and may cause diagnostic challenges. Case In this paper, we present the case of a 36-year-old female patient with a rapidly growing gingival mass. She had a history of undifferentiated skin carcinoma almost 18 months ago. An incisional biopsy was performed, and according to microscopic findings and medical history, a diagnosis of undifferentiated metastatic carcinoma was made. Conclusion Oral metastasis needs to be considered in the differential diagnosis of lesions in patients with a history of malignancy.